Rhetoric of Citizenship and State Surveillance in Kazou Ishiguro’s Never Let Me Go - Giri, Pradip Raj (Tribhuvan University Journal, 2025)
The research critically examines the rhetorical discourse of citizenship in Kazou Ishiguro’s Never Let Me Go. It aims at unraveling the subjugation of people in modern society by exploring the complex identity of narrator and other characters where citizenship have taken the possibility to new level of power politics, redefining security and reality through universalized state. This research critically analyses how the issues of citizenship and immigrations are rhetorically constructed through discourse, in which categorization and Identity play a crucial role in dividing people into different hierarchies based on race, ability, sexuality, and perceived national origin. Instead of understanding that these categories are fixed, natural, or purely legal, this work reveals the way citizenship operate as rhetorical systems that shape how bodies are seen, governed, and valued. The rhetorical acts involved in creating these discourses mirror colonial logic and reinforce exclusion, surveillance, and disposability of some bodies over others. To support the claim, the researcher draws some of the theoretical insight from Bio-Power mainly forwarded by Michel Foucault, Giorgio Agamben’s concept of Bios and Zeos and David Spurr’s concept of Citizenship.